2018
DOI: 10.1242/jeb.161554
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity and fat metabolism during combined fasting and lactation in elephant seals

Abstract: Animals that fast depend on mobilizing lipid stores to power metabolism. Northern elephant seals (Mirounga angustirostris) incorporate extended fasting into several life-history stages: development, molting, breeding and lactation. The physiological processes enabling fasting and lactation are important in the context of the ecology and life history of elephant seals. The rare combination of fasting and lactation depends on the efficient mobilization of lipid from adipose stores and its direction into milk pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 119 publications
(159 reference statements)
3
11
0
Order By: Relevance
“…Weight loss and corticosteroid hormones. Females sampled late in lactation and molting had lower mass and adiposity and elevated circulating corticosteroid levels relative to early fasting groups, consistent with other studies in this species and the known lipolytic and gluconeogenic functions of cortisol that are required to support fasting metabolism (4,7,16). The highest corticosteroid concentrations were measured in late lactation, when milk lipid concentration is highest (16), while the lowest were measured during early molt, when females return from their postbreeding foraging trip.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Weight loss and corticosteroid hormones. Females sampled late in lactation and molting had lower mass and adiposity and elevated circulating corticosteroid levels relative to early fasting groups, consistent with other studies in this species and the known lipolytic and gluconeogenic functions of cortisol that are required to support fasting metabolism (4,7,16). The highest corticosteroid concentrations were measured in late lactation, when milk lipid concentration is highest (16), while the lowest were measured during early molt, when females return from their postbreeding foraging trip.…”
Section: Discussionsupporting
confidence: 87%
“…Females sampled late in lactation and molting had lower mass and adiposity and elevated circulating corticosteroid levels relative to early fasting groups, consistent with other studies in this species and the known lipolytic and gluconeogenic functions of cortisol that are required to support fasting metabolism (4,7,16). The highest corticosteroid concentrations were measured in late lactation, when milk lipid concentration is highest (16), while the lowest were measured during early molt, when females return from their postbreeding foraging trip. Gains in mass and adiposity were higher during the postmolting foraging trip, which is associated with gestation, than during the postbreeding foraging trip, when females mainly replenish protein stores impacted by lactation (1,9,37).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Body CI was negatively associated with cortisol and rT3, which is consistent with a previous study of juvenile elephant seals that found that T4 levels significantly decreased over a fasting period during which animals lost 17% of their body fat ( Kelso et al , 2012 ). Cortisol was also negatively associated with adiposity in lactating adult female elephant seals ( Fowler et al , 2018 ), but not in juveniles ( Kelso et al , 2012 ), highlighting the importance of evaluating stress state in the context of life history stage, especially in fasting-adapted marine mammals. Body condition was also negatively associated with DKK1 , but not with any of the other gene markers, suggesting that this gene may be a novel molecular marker of adiposity in marine mammals.…”
Section: Discussionmentioning
confidence: 99%
“…Northern elephant seals (NES) have an annual cycle that includes months at sea foraging and acquiring body fat, punctuated by extended fasting periods while hauled out on land for molting or pupping/breeding ( Fowler et al, 2018 ). When molting, these seals typically spend ∼40 days on land with the combined catabolic stimuli to skeletal muscle of reduced activity and fasting.…”
Section: Introductionmentioning
confidence: 99%